Medical image reader powered by artificial intelligence - Palok, Tanvir Ahmed; Ahmed, Symum; Anim, Golam Kibria; Ratul, Shahed Sharif Bhuiyan; Alam, Shahrear (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.